Sustainable energy for all or sustainable energy for men? Gender and the construction of identity within climate technology entrepreneurship in Kenya. (April 2017) - Marshall, Mipsie; Ockwell, David; Byrne, Rob
As international climate and development policy and funding efforts accelerate, this article articulates an urgent new research agenda aimed at redressing the existing failure of policy and research to attend to gender in relation to climate mitigation (as opposed to adaptation). Focusing on the transfer and uptake of low carbon energy technologies, including a review of the literature on women and entrepreneurship and critical discourse analysis of the treatment of climate technology entrepreneurs by infoDev (World Bank) in Kenya, the prevalence of private sector entrepreneurial approaches to climate and development policy and practice in this field is demonstrated to be reinforcing gendered power imbalances.